Residue determination and dietary risk assessment of mesotrione, nicosulfuron, atrazine and its four metabolites in maize in China - Chen, Huazhang; Li, Jiewei; Wang, Yuxi; Zhou, Yannan; Duan, Zhengfeng; Duan, Tingting (Frontiers in Sustainable Food Systems, 2023)
To improve maize yield, multiple herbicides have been simultaneously applied to control more weeds. However, such combined use can cause different residues with unknown risks to human health. To promote the sustainability of maize production, the residues and dietary risk of a new herbicide formulation need to be evaluated. First, we developed quick methods to determine the levels of mesotrione, nicosulfuron atrazine, and its four metabolites with acceptable accuracy and precision by UHPLC-MS/MS. Limits of quantification (LOQs) were 0.01 mg/kg for mesotrione and atrazinedesethyl-desisopropyl as well as 0.005 mg/kg for nicosulfuron, atrazine, 6-deisopropyl atrazine, 2hydroxyatrazine and deethylatrazine. The field trials were conducted at 12 locations of China, followed by the determination of terminal residues. In straw samples, the residues were in the ranges of <0.01 mg/kg for mesotrione, <0.005-0.010 mg/kg for nicosulfuron and <0.037-0.254 mg/kg for accumulated atrazine. The levels in green straw were in the ranges of <0.01 mg/kg for mesotrione, <0.005-0.007 mg/kg for nicosulfuron and <0.037-0.211 mg/kg for accumulated atrazine. For green maize and fullygrown maize, the residues were lower than 0.01 mg/kg for mesotrione, 0.005 mg/kg for nicosulfuron and 0.037 mg/kg for accumulative atrazine. According to the risk quotient (RQ) model, the dietary risk assessment of three herbicides showed that all the RQ values were less than 100%, representing acceptable risk by consumers. Therefore, this study helps guide the rational use of mesotrione, nicosulfuron and atrazine to ensure the safe production of maize and our human health.